A diagnostic dilemma of central skull base osteomyelitis mimicking neoplasia in a diabetic patient. (25th January 2013) - Ganhewa, Aparna Dasunmalee; Kuthubutheen, Jafri
Abstract : We present a case which illustrates the diagnostic difficulty in distinguishing between osteomyelitis of the central skull base and base of skull tumours. A woman in her early forties presented with seizures and multiple cranial nerve palsies. She also had a background of chronic otalgia and poorly controlled diabetes mellitus. The clinical diagnosis of skull base osteomyelitis (SBO) was made, but both MRI and bone scans were unable to distinguish this from a skull base malignancy on imaging criteria. Eventually biopsies were required to exclude the diagnosis of malignancy and the patient was treated for central SBO.